Penerapan Metode Role Playing untuk Meningkatkan Hasil Belajar IPS SD Materi Kegiatan Ekonomi Indonesia - Abdurrahim (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2021)
The results of social studies learning material on Indonesian economic activities for fifth grade students of SD Negeri 003 Singkep Barat, Lingga Regency, have not reached the minimum completeness criteria. This happened because social studies learning material on Indonesian economic activities at SD Negeri 003 Singkep Barat had only used the lecture method. The role playing method is assumed to be able to improve social studies learning outcomes for fifth graders at SD Negeri 003 Singkep Barat. The purpose of this classroom action research is to describe that the application of the role playing method can improve social studies learning outcomes for Indonesian economic activity materials in fifth grade students at SD Negeri 003 Singkep Barat, Singkep Barat District, for the 2019/2020 school year. This research is classroom action research, which consists of two cycles. Each cycle consists of two meetings. Each meeting was carried out through a number of stages, namely: planning, acting, observing, and reflecting. The results showed that the percentage of student learning completeness from cycle I to cycle II increased. In the first cycle, it reached 77% to 100% at the end of the second cycle. Based on the results of the study, it can be concluded that the application of the role playing method can improve social studies learning outcomes for the fifth grade students of SD Negeri 003 Singkep Barat, Lingga Regency.